Kesiapan Pembelajaran E-Learning Sekolah Dasar di Banyumas - Anna Sukmawati Kusyanto; Subuh Anggoro (Jurnal Inovasi Pendidikan Dasar, 2021)
This study aims to determine the readiness of teachers, students, and parents in the e-learning process. The methodology of this research was qualitative research. The participants in this study were 46 teachers, 178 students, 117 students' parents. The data collection technique was an observation, questionnaires, and interviews. The result showed that teachers were ready to use e-learning in learning seen from teachers who already understood e-learning and applied e-learning. Furthermore, the number of students who felt more comfortable, happy to follow e-learning. Nevertheless, the many parents who were busy with work were not ready to be seen, so they could not assist students in the learning process. Keywords: e-learning, readiness, elementary school